Effects of salinity and pH on the spectral induced polarization signals of graphite particles. Issue 3 (20th February 2020) - Wu, Yuxin; Peruzzo, Luca
SUMMARY: The electrical property of micrometre-sized graphite particles was investigated under different particle concentration, particle size, fluid conductivity and pH conditions. Due to its large internal electronic conductivity and ability to polarize under external potential field, significant enhancement of its spectral induced polarization (SIP) responses is observed when graphite is included in sand mixtures. While a small amount of graphite inclusion significantly increases the SIP response of its mixtures with sand, further concentration increase does not necessarily lead to a proportional increase of the SIP response. This is shown to be related to the formation of graphite aggregates at higher concentrations. Changes of fluid salinity have a significant effect on graphite's SIP behaviour. This includes a positive impact on normalized chargeability and imaginary conductivity, but a negative impact on chargeability and relaxation time constant. The effect of pH on the SIP response of graphite is small but shows consistent trend, where pH increase leads to a decrease of both the chargeability and relaxation time constant. The underlying cause of this effect is not clear.